Recognizing biography - Epstein, William H. (University of Pennsylvania Press, 1987)
Epstein's narrative interweaves interpretive and theoretical chapters as it emplots the discourse of English biography from Walton to Strachey. In this way familiar generic relationships between biographer, subject, life, text, falsehood, and readership are analyzed in specific (if constantly shifting) historical, literary, cultural, and economic texts.
Keywords: English prose literature -- History and criticism.; Biography as a literary form.; Biography.; Biographies as Topic.; Biographie (Genre littéraire); Prose anglaise -- Histoire et critique.; Biographies.; biographies (literary genre); biography (general genre); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM / Semiotics & Theory; Biography as a literary form; English prose literature; Biografieën.; Engels.; Biographie (genre littéraire); Cultural Studies.; Literature.; Criticism, interpretation, etc.